2020
DOI: 10.1080/17482631.2020.1732526
|View full text |Cite
|
Sign up to set email alerts
|

Promoting wellbeing and health through active participation in music and dance: a systematic review

Abstract: Purpose: This review aims to reveal how music and dance participation relates to key social determinants of health, and acts as population wellbeing and health promotion and preventive tools for people without pre-existing health issues in diverse social groups. Methods: A qualitative systematic literature review addresses the questions: 1) How might music and dance cultural practices relate to social determinants of health?; 2) What gaps exist in the current body of research examining how healthy individuals/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 65 publications
2
80
0
6
Order By: Relevance
“…The percentage of female respondents was also much higher than that of male respondents. However, this is a known problem very often found in survey studies in general (e.g., Justo-Alonso et al, 2020 ; Sandín et al, 2020 ) and in studies on the effects of music-related activities on emotional wellbeing in particular (e.g., Livesey et al, 2012 ; Krause et al, 2019 ; Saarikallio et al, 2020 ; Sheppard and Broughton, 2020 ). We should also note that this study only focused on adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of female respondents was also much higher than that of male respondents. However, this is a known problem very often found in survey studies in general (e.g., Justo-Alonso et al, 2020 ; Sandín et al, 2020 ) and in studies on the effects of music-related activities on emotional wellbeing in particular (e.g., Livesey et al, 2012 ; Krause et al, 2019 ; Saarikallio et al, 2020 ; Sheppard and Broughton, 2020 ). We should also note that this study only focused on adults.…”
Section: Discussionmentioning
confidence: 99%
“…In times when psychological welfare is threatened, research on strategies that can be helpful to promote positive emotions is of great relevance. Among those, music-related activities are considered especially useful, being these available to everyone and an easy and low cost means to enhance wellbeing ( Dingle et al, 2017 ; Daykin et al, 2018 ; Kappert et al, 2019 ; de Witte et al, 2020 ; Sheppard and Broughton, 2020 ). Not in vein, when considering the psychological functions of music, the socioemotional uses of musical behaviors (e.g., either music listening or music performance) have been traditionally highlighted ( Hargreaves and North, 1999 ; Schäfer et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…To prevent a decrease in PA, various interventional programs have been constructed to encourage children and adolescents to be more physically active [ 10 , 11 ]. Since such programs should be motivational and attractive, dance is a perfect tool, as it fulfils not only PA requirements but also enables the development of social skills and expressiveness in youth [ 12 , 13 , 14 ]. As some individuals begin to dance very early in their childhood, dance is a particularly suitable form of PA that can be continuously applied whether in a professional or recreational context, throughout a participant’s lifetime [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ventegodt et al [42] call this spectrum the integrative quality-of-life (IQOL) theory and this is the theoretical aspect assumed in this study. A recent systematic review provided substantial evidence that music and dance activities enhance participants' physical, cognitive, and social determinants of health (such as stress, social isolation, autonomy) and individual wellbeing across all groups, and interventions can be highly effective and able to be adequately maintained [43]. Most of the studies in this review showed significant improvements in cognitive function, revealed significant overall effects in favour of dance, which are moderate for a useful way to boost cognitive function, and may reduce the risk for cognitive disorders in older adults, especially with metabolic syndrome [34].…”
Section: Discussionmentioning
confidence: 99%